Defining Soil and Water Assessment Tool (SWAT) hydrologic response units (HRUs) by field boundaries - Kalcic, Margaret M.; Chaubey, Indrajeet; Frankenberger, Jane (International Journal of Agricultural and Biological Engineering, 2015)
The Soil and Water Assessment Tool (SWAT) is widely used to relate farm management practices to their impacts on surface waters at the watershed scale, yet its smallest spatial unit is not generally defined by physically meaningful boundaries. The hydrologic response unit (HRU) is the smallest spatial unit of the model, and the standard HRU definition approach lumps all similar land uses, soils, and slopes within a subbasin based upon user-defined thresholds. This standard method provides an efficient way to discretize large watersheds where simulation at the field scale may not be computationally feasible. In relatively smaller watersheds, however, defining HRUs to specific spatial locations bounded by property lines or field borders would often be advantageous, yet this is not currently possible within the ArcSWAT interface. In this study, a simple approach is demonstrated that defines HRUs by field boundaries through addition of uniquely named soils to the SWAT user soil database and creation of a field boundary layer with majority land use and soil attributes. Predictions of nitrogen, phosphorus, and sediment losses were compared in a case study watershed where SWAT was set up using both the standard HRU definition and field boundary approach. Watershed-scale results were reasonable and similar for both methods, but aggregating fields by majority soil type masked extremely high soil erosion predicted for a few soils. Results from field-based HRU delineation may be quite different from the standard approach due to choosing a majority soil type in each farm field. This approach is flexible such that any land use and soil data prepared for SWAT can be used and any shapefile boundary can divide HRUs.Keywords: watershed, modeling, Soil and Water Assessment Tool (SWAT), hydrologic response units, field boundaries, common land units, landuse managementDOI: 10.3965/j.ijabe.20150803.951 Online first on [2015-03-03]Citation: Kalcic M M, Chaubey I, Frankenberger J. Defining Soil and Water Assessment Tool (SWAT) hydrologic response units (HRUs) by field boundaries. Int J Agric & Biol Eng, 2015; 8(3): 69－80.